SPEECH DEVELOPMENT OF YOUNGER SCHOOL STUDENTS USING CHILDREN’S LITERATURE AND DIGITAL TOOLS - Kachak, Tetiana; Blyznyuk, Tetyana; Hryvnak, Mariana (Mountain School of Ukrainian Carpaty, 2023)
The article theoretically elaborates on the problem of speech development of younger school students and offers an effective model of its solution in the practice of the New Ukrainian School (NUS) by means of children’s literature and digital tools. It is noted that the main task of students’ development is to master speaking skills as a means of communication, cognition, and expression of feelings. Analysing and discussing what has been read, comprehending children’s literature texts, and expressing their own opinions and assessments are the key to the active oral and written monologic and dialogic speech of schoolchildren. In modern educational realities, these aspects significantly enhance digital tools that are used as means of visualisation, analysis, systematisation, and discussion of what has been read, organisation of communicative and interactive cooperation between students. The proposed and tested methodological model of speaking skills development of primary school students is based on the systematic and purposeful use of, firstly, a literary text and its analysis for the development of students’ monologic and dialogic speech, and, secondly, digital resources. This is demonstrated by the example of the methodological development of a fragment of a literary reading lesson for the 3rd grade on the topic «Oleksandr Dermanskyi «Biliachok»». Interactive exercises «Cluster», «Six thinking hats», tasks and games created in the LearningApps online service, as well as mind maps, and interactive posters, the content of which is based on the analysis of the read work, not only motivate students to active communication, presentation, and evaluation of information but also make the learning process interesting, exciting, modern, well visualised. Thus, the synthesis of children’s literature and digital tools as a means of developing speech of younger school students is an effective methodological model for solving the problem.